2021
DOI: 10.1108/jfc-05-2021-0107
|View full text |Cite
|
Sign up to set email alerts
|

The Covid-19 impact on financial crime and regulatory compliance in Malaysia

Abstract: Purpose The purpose of this paper is to provide a conceptual discussion and analysis of the Covid-19 impact on financial crime and regulatory compliance. The analysis is conducted to make a comparison of the financial crime and regulatory compliance patterns before and after the Covid-19 pandemic occurred. Design/methodology/approach This paper contextualises the impact of Covid-19 on financial crime and regulatory compliance. Moreover, this paper explores different ways of conceptualising the Covid-19 impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…Regulators, preparers, and auditors have described the June 2020 financial reporting period as one of the most challenging reporting periods ever, as reporting entities were faced with uncertainty due to the COVID-19 pandemic (Kend and Nguyen, 2022). Also, the epidemic's effects on e-commerce and the advancement of financial technology's digitization have both accelerated dramatically (Jamil et al, 2022). However, thus far, there is little about how changes in the COVID-19 environment have affected audit tasks completed by auditors, including judgments on what to include in audit reports and the informational value of those reports to investors.…”
Section: Now the Research Shows Studies That Have Shown High Audit Risksmentioning
confidence: 99%
“…Regulators, preparers, and auditors have described the June 2020 financial reporting period as one of the most challenging reporting periods ever, as reporting entities were faced with uncertainty due to the COVID-19 pandemic (Kend and Nguyen, 2022). Also, the epidemic's effects on e-commerce and the advancement of financial technology's digitization have both accelerated dramatically (Jamil et al, 2022). However, thus far, there is little about how changes in the COVID-19 environment have affected audit tasks completed by auditors, including judgments on what to include in audit reports and the informational value of those reports to investors.…”
Section: Now the Research Shows Studies That Have Shown High Audit Risksmentioning
confidence: 99%
“…Covid-19 is a new strain of SARS (SARS-CoV-2) which has spread throughout several nations, becoming a worldwide epidemic (WHO, 2020). To adhere to social distance instruction, many companies in Malaysia were required to shift their normal working arrangement to WFH (Jamil et al,2021). WFH can be defined as performing work activities by utilizing technology at home or an alternate location to the workplace (Imhanrenialena et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research has found that Covid-19 has a variety of effects, including on people's health (Boyle et al, 2020;Xiang et al, 2021), e-commerce (Jlkova & Kralova, 2021;Bhatti et al, 2020;Sayyida et al, 2021), education (Daniel, 2020;Kogan et al, 2020), and criminal (Jamil et al, 2021;Hawdon, Parti & Dearden, 2020;Tharshini, Hassan, & Mas'ud, 2021;Ashby, 2020). For instance, Jamil et al (2021) point out that Covid-19 and related measures have an impact on both physical and online criminalization.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has found that Covid-19 has a variety of effects, including on people's health (Boyle et al, 2020;Xiang et al, 2021), e-commerce (Jlkova & Kralova, 2021;Bhatti et al, 2020;Sayyida et al, 2021), education (Daniel, 2020;Kogan et al, 2020), and criminal (Jamil et al, 2021;Hawdon, Parti & Dearden, 2020;Tharshini, Hassan, & Mas'ud, 2021;Ashby, 2020). For instance, Jamil et al (2021) point out that Covid-19 and related measures have an impact on both physical and online criminalization. Prior studies (Nivette et al, 2021;Boman & Gallupe, 2020;Ashby, 2020;Campedelli et al, 2021;Gerell et al, 2020;Halford et al, 2020;Hodgkinson & Andresen, 2020;Mohler et al, 2020;Langton et al, 2021) highlight that the nationwide lockdown, which obliged residents to remain at home, had a positive and considerable influence on reducing physical crimes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation